New database of bottom trawl stations performed in the Far-Eastern Seas and the North Pacific in 1977-2010 - Igor V. Volvenko (Известия ТИНРО)
New database (DB) is presented of 224 fishery-independent bottom trawl surveys (32699 trawl stations) conducted in the last 34 years in the North Pacific and adjacent regions - the Bering, Okhotsk, and Japan/East. Bottom surveys embrace the depth range from 5 to 2025 m, so they cover less area than pelagic ones. The majority of the trawls (30510) are obtained in the areas of regular monitoring of biological resources and state of ecosystems (2 mln km2). More than 1400 species of fish and invertebrates with the body size ≥ 1 cm are presented in the bottom trawl catches. Each of 459660 DB records on registered species has at least number and/or weight specification and size measurements data. History of DB creation and improvement of its quality is overviewed and the first operating experience is shared, with special attention to its advantages and ways of further development. Role of DB in the framework of the Concept of Ecological Safety of Russia is considered. Its imperfections are discussed as the lack of fishery-independent trawl surveys after 1990 and insufficient number of deep-water trawls, that causes a problem of interannual incomparability. However, in spite of data incompleteness and some methodical problems of surveys, the huge number of marine expeditions conducted by Pacific Fish. Res. Center (TINRO) in the last decades allows to operate with unprecendented volume of information on composition and structure of bottom macrofauna over the vast area of shelf and continental slope. Sure that no other institution in the world ever had, has, and probably will have in a foreseeable future a better material for studying of benthic biocenoses.